The relationship between the moderate-heavy boundary and critical speed in running - Hunter, B.; Meyler, S.; Maunder, E.; Cox, T. H.; Muniz-Pumares, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose Training characteristics such as duration, frequency, and intensity can be manipulated to optimize endurance performance, with an enduring interest in the role of training-intensity distribution to enhance training adaptations. Training intensity is typically separated into 3 zones, which align with the moderate-, heavy-, and severe-intensity domains. While estimates of the heavy- and severe-intensity boundary, that is, the critical speed (CS), can be derived from habitual training, determining the moderate-heavy boundary or first threshold (T1) requires testing, which can be costly and time-consuming. Therefore, the aim of this review was to examine the percentage at which T1 occurs relative to CS.